Consensus regarding the diagnosis, prognosis and treatment of canine mammary tumors: Benign mixed tumors, carcinomas in mixed tumors and carcinosarcomas - Cassali, Geovanni D.; Damasceno, Karine A.; Bertagnolli, Angélica C.; Estrela-Lima, Alessandra; Lavalle, Gleidice E.; Di Santis, Giovana W.; De Nardi, Andrigo B. [UNESP]; Fernandes, Cristina G.; Cogliati, Bruno; Sobral, Renata; Amorim da Costa, Fernanda V.; Ferreira, Enio; et al. (Brazilian Journal of Veterinary Pathology, 2017)
Mammary neoplasms are the most frequent tumors in female dogs. Of these neoplasms, benign mixed tumors (BMTs) and carcinomas in mixed tumors (CMTs) represent a large proportion of small animal oncology diagnoses. Together with carcinosarcomas (CSs), these three neoplastic entities are characterized by the proliferation of benign or malignant epithelial, myoepithelial, and mesenchymal cells, depending on their histological types. This histological heterogeneity, in addition to their molecular heterogeneity, confers these tumors with distinct biological behavior, which results in the need for different clinical and therapeutic approaches. The present consensual document elucidates the oncological issues related to the diagnosis, prognosis, and treatment of BMTs, CMTs, and CSs of the canine mammary gland.
Keywords: Dogs; Mammary gland; Mixed tumours; Oncology; Veterinary